Extraction and separation of heavy rare earth elements: A review - Liu, Tianchi; Chen, Ji (Separation and purification technology, 2021)
•A detailed summary on the advanced technologies for the separation of HREEs was proposed.•The sources, distribution, leaching, extraction and separation of HREEs were in depth discussed.•Evaluations of each method and essential perspectives for future researches were put forward.•Theoretical guides was provided for the recovery and preparation of high-purity HREEs. Heavy rare earth elements (HREEs) containing Gd to Lu plus Y have a series of unique physicochemical properties which endow them critical resources in many fields such as high-tech components, green technologies and material industries. However, the huge demand of HREEs has resulted in sharply reduction of their reserves. Henceforth, it is necessary to efficiently0020separate and recover HREEs using some simple and commercially viable methods. The present review makes a detailed summary on the advanced technologies for the separation and purification of HREEs in recent ten years including both liquid-liquid extraction (LLE) and solid-liquid separation (SLP). Further understandings of the crucial scientific issues such as sources, distribution, and leaching, as well as extraction background, extraction theory, extraction technology, separation efficiency and adsorption capacity, were also in depth discussed. Evaluations of each method and essential perspectives for future researches were proposed in the end of this review. Meanwhile, this review should provide theoretical guides for the preparation of high-purity HREEs and references for the recovery of HREEs from the actual production.